KNOWLEDGE AND UNDERSTANDING OF LAW: THEORETICAL AND LEGAL VIEWS OF S. S. ALEKSEEV (EUROPEAN AND ASIAN LAW REVIEW, 2024)
This work examines, explores and analyzes scientific thoughts, ideas and views about the law of the outstanding Soviet and Russian scientist of our time Alekseev Sergey Sergeevich. Close attention is paid to the concept of legal understanding by scientist, his relation to the legal system, its structure, properties, relationships between elements, as well as the prospects for the development of law, expressed by the theorist at the awarding of the Demidov Prize in 2010.
Keywords: Alekseev Sergey Sergeevich; knowledge of law; legal understanding; system of law; structure of law; properties of law; legal norm